Emotional freedom techniques for treating post traumatic stress disorder: an updated systematic review and meta-analysis - Stapleton, Peta; Kip, Kevin; Church, Dawson; Toussaint, Loren; Footman, Jacqui; Ballantyne, Pat; O’Keefe, Tom (Frontiers in Psychology, 2023)
Clinical Emotional Freedom Techniques (EFT) is a psychophysiological intervention that includes cognitive and somatic elements, utilizing techniques from both Cognitive Behavioral Therapy (CBT) and Prolonged Exposure therapy (PE). Because only a single meta-analysis existed examining EFT for PTSD, this systematic review and meta-analysis represents an update. Ten databases were searched for quantitative reviews and randomised clinical trials, and six met inclusion criteria. Study quality and effect size were evaluated and the results demonstrated that treatment with Clinical EFT, when compared to wait list, usual care, or no treatment controls, resulted in significant and large effect sizes, ranging from 1.38 to 2.51. When compared to active controls, effect sizes ranged from -0.15 to 0.79, producing treatment results similar to other evidence-based therapies. Limitations are presented and considerations for further research are proposed.